Report of the Auditor General of Canada to the House of Commons, 1992-93 - Canada Office of the Auditor General (The Office, 1993)
This document includes matters of special importance and interest, follow-up and other audit observations, studies, and appendices, which include the Auditor General Act, the Financial Administration Act, with extracts from Part X, and reports from standing committees. Also includes audit scopes, observations, recommendations and conclusions from departments.